Implementasi Sistem Informasi Manajemen dalam Pendidikan Sekolah di Masa Pandemi covid 19 - Eka Yanti; Rayyan Firdaus (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
It is very important to implement an information system during the pandemic. Having this information system will make it easier for all parties to understand and understand how educational information can be implemented well. Optimal education can be given or received by all parties in it, such as teachers, lecturers, pupils, university students and so on, regardless of basic or higher education, it is hoped that they will be able to maximize the various collections and applications of the information system. As for the aim of the author of this article is to describe the implementation of management information systems in improving education during the pandemic using literature studies that analyze journals, books and other sources. The author uses descriptive literature studies by selecting sources through journal articles that are relevant to the Covid-19 pandemic